A Case of Psychosis and Renal Failure Associated with Excessive Energy Drink Consumption - D. Kelsey; A. J. Berry; R. A. Swain; S. Lorenz (Case Reports in Psychiatry)
Energy drinks are nonalcoholic beverages that are widely consumed in the general population, and worldwide usage is increasing. The main stimulant component of energy drinks is typically caffeine. Few case reports exist that link energy drink consumption to psychosis, and similarly few reports exist that associate energy drink consumption with acute renal failure. We present a patient who simultaneously developed psychosis and acute renal failure associated with excessive energy drink consumption. The patient required haemodialysis, and his psychosis resolved on cessation of energy drinks and a brief course of antipsychotic medication. We perform a review of similar cases where excessive caffeinated energy drink consumption has been linked to psychosis or acute renal failure. To our knowledge, this is the first case report describing both renal failure and psychosis occurring simultaneously in a patient. Recognising the spectrum of disorders associated with excessive energy drink consumption is vital for both physicians and psychiatrists, as this has important implications for both prognosis and treatment.